Line Source Scattering by Buried Perfectly Conducting Circular Cylinders. (7th August 2012) - Frezza, F.; Pajewski, L.; Ponti, C.; Schettini, G.
Abstract : A two-dimensional scattering problem of a line source by a set of perfectly conducting circular cylinders buried in a semi-infinite medium is solved, in both TE and TM polarization. A cylindrical-wave approach is used and applied to both the field emitted by the source and the field scattered by the buried objects. Reflection and transmission of such fields through the planar interface are evaluated making use of the plane-wave spectrum of a cylindrical wave. Numerical results are presented, with checks confirming the validity of the method.